IDH genotypes differentiation in glioblastomas using DWI and DSC-PWI in the enhancing and peri-enhancing region. (December 2019) - Xing, Zhen; Zhang, Hua; She, Dejun; Lin, Yu; Zhou, Xiaofang; Zeng, Zheng; Cao, Dairong
Background: Isocitrate dehydrogenase (IDH) mutation has diagnostic and prognostic values in glioblastomas. Peritumoral invasion of glioma cells is a cardinal feature of glioblastomas. Purpose: To evaluate the contribution of DWI and DSC-PWI in the enhancing and peri-enhancing region for discriminating glioblastomas IDH genotypes, and the diagnostic values of combining two techniques in the peri-enhancing region compared with those in the enhancing region. Material and Methods: We retrospectively reviewed the conventional MRI (cMRI), DWI and DSC-PWI obtained from 10 patients with IDH-mutated (IDH-m) glioblastomas and 65 patients with IDH wild-type (IDH-w) glioblastomas. Features of cMRI, relative minimum ADC in the enhancing region (rADCmin-t ) and peri-enhancing area (rADCmin-p ), and relative maximum CBV values in the enhancing region (rCBVmax-t ) and peri-enhancing region (rCBVmax-p ) were compared between two groups. Receiver operating characteristic curves and logistic regression analysis were used to assess diagnostic performance. Results: IDH-m glioblastomas tended to present in frontal lobes and younger patients. The rADCmin-t ( P  = 0.042) were significantly lower in IDH-w than IDH-m. Both rCBVmax-t and rCBVmax-p showed significant differences between two subgroups (all P  < 0.001). The optimal cutoff values in prediction of IDH-m were >0.98 for rADCmin-t, <7.27 for rCBVmax-t, and < 0.97 for rCBVmax-p . Multivariate logistic regression revealed that the combination of rADCmin-t and rCBVmax-t yielded the highest sensitivity and specificity. Conclusion: The rCBVmax-t or rCBVmax-p may serve as preferable and comparable imaging biomarkers for evaluation of glioblastomas IDH status. The combination of rADCmin-t and rCBVmax-t may yield the maximum predictive power for differentiating IDH status.